O potrzebie opracowania dziejów kresowej polszczyzny nowogródzkiej - Lewaszkiewicz, Tadeusz (Slavia Occidentalis, 2023)
The Polish dialect of Novogrudok is one of the variations that make up the North Borderlands Polish language, next to the Vilnius and Kaunas dialects, to name just two. A detailed study of this regional historical Polish dialect is important because of the history of the Polish language spoken in the North Borderland, and primarily due to the possible enrichment of the knowledge of the language used by Adam Mickiewicz. The article contains the names of authors and titles of 16th to 19th century works that might be useful in writing the history of the Polish dialect spoken in Novogrudok.